Challenges in the Teaching and Learning of Textiles in the Primary School Curriculum in Masvingo District Zimbabwe - Mupfumira, Isabel Makwara; Nyaruwata, Leonora T. (Asian Journal of Contemporary Education, 2021)
The purpose of this research was to conduct an analysis of the challenges faced in the teaching and learning of Textiles in the primary school curriculum in Masvingo district Zimbabwe. The study was informed and guided by two theories namely the concerns-based adoption model (CBAM) and the pragmatist’s theory. A qualitative case study design was employed to allow for naturalistic methods of data collection. The study was conducted at five selected primary schools in Masvingo district, Masvingo province in Zimbabwe. The population of the study comprised teachers, parents, school development committee (SDC) chairpersons, school heads and the schools inspector. Convenience and purposive sampling was employed to get a total of 54 participants. The data was collected using interviews, observation and document analysis. The major findings of the research were that schools lacked facilities for effective teaching and learning of Textiles in form of personnel, infrastructure, equipment and consumables especially in rural schools. The other finding was that the nature of the Grade 7 examination created a negative attitude towards teaching and learning of Textiles. The study recommends that the Government should take a lead in creating a conducive learning and teaching environment for Textiles through provision of both human and material resources. The examination system should give equal status to all subjects assessed in the general paper.